2021
DOI: 10.1101/2021.11.13.468347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-dimensional structure of kinetochore-fibers in human mitotic spindles

Abstract: During cell division, kinetochore microtubules (KMTs) provide a physical linkage between the spindle poles and the chromosomes. KMTs in mammalian cells are organized into bundles, so-called kinetochore-fibers (k-fibers), but the ultrastructure of these fibers is currently not well characterized. Here we show by large-scale electron tomography that each k-fiber in HeLa cells in metaphase is composed of approximately nine KMTs, only half of which reach the spindle pole. Our comprehensive reconstructions allowed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 91 publications
3
30
0
Order By: Relevance
“…The presence of these MTs at most KTs during the earliest stages of spindle formation has been demonstrated 26,55,56 and incorporation of MTs nucleated at the KT into K-fibers appears to continue throughout mitosis. 57 Live-cell microscopy demonstrates that MTs that are nucleated at KT develop into bundles that grow outward and eventually connect to the spindle poles. 27,32,33,58,59 However, how the initial array of MTs at the KT converts into a K-fiber with proper polarity is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these MTs at most KTs during the earliest stages of spindle formation has been demonstrated 26,55,56 and incorporation of MTs nucleated at the KT into K-fibers appears to continue throughout mitosis. 57 Live-cell microscopy demonstrates that MTs that are nucleated at KT develop into bundles that grow outward and eventually connect to the spindle poles. 27,32,33,58,59 However, how the initial array of MTs at the KT converts into a K-fiber with proper polarity is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…First, we assumed that the k-fiber is mechanically homogeneous along its length. Electron microscopy of spindles revealed that k-fiber microtubules decrease in number closer to the pole (McDonald et al 1992), and that their length and organization can vary depending on the system (O' Toole et al 2020, Kiewisz et al 2021. These factors can affect the k-fiber's flexural rigidity along its length (Ward et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…During this gradual process, laterally attached kinetochores rarely detach in the presence of CENP-E, while kinesin-13 MCAK is required for efficient removal of kinetochore attachments to the lateral walls of the MT (Figure 3D) [96]. Since the vertebrate kinetochore is bound by 10-30 MTs [98][99][100], both the wall-tethering and the gliding model of the CENP-E function agree that end-on conversion is likely to be a gradual process in which some MTs at first remain bound laterally to kinetochores, while some become end-on attached, known as mixed lateral end-on attachment [96] (Figure 3B). A list of potential functions of kinetochore-associated CENP-E does not end here, as CENP-E has also been demonstrated to be a processive bi-directional tracker of dynamic MT tips [53], CENP-E can regulate the SAC through its interaction with BubR1 kinase [101], and both are important for stabilization of kinetochore-MT end-on attachments.…”
Section: Getting To the Equator-congression From The Spindle Pole To ...mentioning
confidence: 99%